Eleanor and Franklin the story of their relationship, based on Eleanor Roosevelt's private papers - Lash, Joseph P. 1909-1987 (W.W. Norton & Co., 1971)
Gives insight into Eleanor's childhood, how she overcame personal insecurity, how she coped as a politician's wife, and describes her relationship with her husband, Franklin.